Detection of phenotypic and molecular fashioned virulence factors of the bacterium Staphylococcus spp. Analyst of blood and isolated from urinary tract infections in Diwaniya - Ali Abed Al-Rahim Al-Nashi; Riyam Wissam Hassan Al- Mansouri (Al-Qadisiyah Journal of Pure Science, 2018)
Collected 180 samples of urine from reviewers patients to Diwaniya Teaching Hospital and Women's Hospital and children education in the city of Diwaniya, for the period from 01/09/2015 until 31/01/2016 and both sexes, To isolate the bacterium Staphylococcus spp. that causes inflammation of the urinary tract and to determine the virulence factors phenotypic and molecular, It found that the rate of 120 (66.66%) samples gave moral growth of bacteria, while 60 increased by (33.33%) a negative sample. It has been found that the isolation of 24 belonging to the bacteria Staphylococcus spp. Distributed on 20 isolated by (16.67%) belonging to the bacteria Staphylococcus aureus and 4 isolates by (3.33%) belonging to the bacteria Staphylococcus haemolyticus of the total samples positive for culture, The isolates producing hemolysin and hemolytic has included all isolates of Staph. aureus and Staph. haemolyticus, Using polymerase chain reaction technique (PCR) proved that genes hlB and hlA exist in bacteria Staphylococcus spp. They encoded to produce hemolysin as it was characterized by all isolates of Staph. aureus analyst blood its proximity to the gene hlA by (100%) and the gene hlB by (40%), when you make detection of genes hemolysin in Staph. haemolyticus appears having gene hlA the rate of (75%) and gene hlB which increased by 25%. The investigation of some virulence factors associated with pathodenicity of bacterial isolates analyst for the blood which included the formation capsule, agglutination of red blood cells and the production of biofilm. produced isolates Staph. aureus and Staph. haemolyticus capsule (40%, 25%) respectively the results of statistical analysis showed no significant differences between them at the level of (P> 0.05), As for the ability of the isolates the agglutination of red blood cells marked by Staph. aureus ability to events agglutination and by (30%) while the all isolates of Staph. haemolyticus unable to events agglutination the results of statistical analysis showed that there were significant differences at the level (P<0.05). also showed bacterial species, an analyst for the blood  the ability to produce biofilm at different rates, As it reached isolates producing biofilm ratio (45% and 50%) of bacteria Staph. aureus and Staph. haemolyticus  respectively.